Elite statecraft and election administration bending the rules of the game? - James, Toby S. (Houndsmills Palgrave Macmillan, 2012)
The way in which elections are run is changing, as radical reforms or experiments have been introduced across the world. This book establishes why election administration might be used by political elites to win and maintain power. It identifies the role of elite interests in shaping election administration in USA, UK and Ireland.
Includes bibliographical references (p. 234-268) and index.
Keywords: Elections